2017
DOI: 10.1016/j.tibs.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Themes in Regulation of Global mRNA Turnover in cis

Abstract: Messenger RNA (mRNA) is the molecule that conveys genetic information from DNA to the translation apparatus. mRNAs in all organisms display a wide range of stability, and mechanisms have evolved to selectively and differentially regulate individual mRNA stability in response to intra-cellular and extra-cellular cues. In recent years, three seemingly distinct aspects of RNA biology—mRNA N6-methyladenosine (m6A) modification, alternative 3’ end processing and polyadenylation (APA), and mRNA codon usage—have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 89 publications
1
35
0
Order By: Relevance
“…2 and 3) suggest that G3BP1 binding to mRNA is positively correlated with mRNA stability, and that this positive correlation can be affected by manipulation of m 6 A levels. mRNA stability in cis is mediated by three major factors: (1) the extent of m 6 A presence, (2) polyadenylation and (3) codon optimization 51 . Of these three factors, m 6 A is the only one that can be dynamically altered through methylation and demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3) suggest that G3BP1 binding to mRNA is positively correlated with mRNA stability, and that this positive correlation can be affected by manipulation of m 6 A levels. mRNA stability in cis is mediated by three major factors: (1) the extent of m 6 A presence, (2) polyadenylation and (3) codon optimization 51 . Of these three factors, m 6 A is the only one that can be dynamically altered through methylation and demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…While this argues against methylation removal in the cytoplasm, internal m 6 A removal by a demethylase such as ALKBH5 within the nucleus could not be excluded and remains possible (Ke et al 2017). Numerous aspects of RNA biology and metabolism have been reportedly regulated by m 6 A mRNA modification, including nuclear processing and export (Fustin et al 2013;Zheng et al 2013Zheng et al , 2017Haussmann et al 2016), translation (Meyer et al 2015;Coots et al 2017;Zhou et al 2018), and mRNA decay Du et al 2016;Chen and Shyu 2017;Edupuganti et al 2017). In addition, mRNA modification by m 6 A influences development, differentiation, reprogramming, circadian rhythm, cell cycle, disease pathogenesis, and stress responses (Fustin et al 2013;Aguilo et al 2015;Merkestein et al 2015;Zhou et al 2015;Vu et al 2017;Wojtas et al 2017;Wen et al 2018).…”
mentioning
confidence: 99%
“…There may also be context‐dependent differences in transcript structure caused by alternative splicing and alternative polyadenylation as well as enzymatic modification that allow transcripts to include or exclude certain regulatory elements . We observed that several annotated transcripts fall short of the full 3′UTR length while investigating the AREs in cell cycle regulators, notably, some of these have since been updated, however, it seems likely that determining transcript structures within the cells of interest will be helpful when considering regulatory sequences.…”
Section: The Zfp36 Family Cell Cycle Regulon In Other Physiological Omentioning
confidence: 88%